Export performance in South America: do intangibles affect firms' performance in developing countries such as Peru? - Del Castillo Guardamino, Carlos (2021)
This study is one of the first empirical studies on intellectual capital (IC) in South American textile exporting companies. Using the resources and capabilities approach, we examine how certain intangibles can provide competitive advantages. We propose and test a model capturing the relationships between IC components and export performance (EP), as well as the various interrelationships among the different dimensions of IC. Using a sample of textile manufacturers operating in Peru, an emerging economy, we find that both human capital and structural capital have a significantly positive influence on EP. However, the data analysis does not confirm that relational capital has any positive influence on export performance.